Patient selection and training for home hemodialysis. (April 2015) - Rioux, Jean‐Philippe; Marshall, Mark R.; Faratro, Rose; Hakim, Raymond; Simmonds, Rosemary; Chan, Christopher T.
Abstract: Patient selection and training is arguably the most important step toward building a successful home hemodialysis (HD) program. We present a step‐by‐step account of home HD training to guide providers who are developing home HD programs. Although home HD training is an important step in allowing patients to undergo dialysis in the home, there is a surprising lack of systematic research in this field. Innovations and research in this area will be pivotal in further promoting a higher acceptance rate of home HD as the renal replacement therapy of choice.